Jak chrześcijaństwo stworzyło cywilizację techniczną w „zaczarowanym [jeszcze] świecie”? - Adamski, Krzysztof (Społeczeństwo, 2024)
This text highlights the underestimated contribution of broadly understood Christianity to the development of technological civilization. This would not have been possible without an entirely new understanding of the concept of human freedom brought about by the Christian faith. This new understanding of freedom, completely different from the one in the ancient theocratic system, by recognizing the role of the human person, led to the liberation of creativity in the areas of economic initiative and technological ingenuity. In the modern era, economic freedom became a subject of moral reflection for the Church. This work provides numerous examples of technical and economic innovation carried out by believers and discusses the necessity of developing a moral science that is adequate to new challenges. The reference point for the presented considerations is Max Weber’s concept of the “disenchantment of the world” and its interpretation by Franz-Xavier Kaufmann.